Circulating immune complexes in children with rheumatic fever - Sarıkayalar, Fikriye; Bakkaloğlu, Ayşın (The Turkish Journal of Pediatrics, 1988)
The circulating immune complexes in rheumatic fever patients with various clinical presentations were investigated by the Raji-cell radioimmunoassay technique. The Jones Criteria was used for guidance in the diagnosis of 38 rheumatic fever patients and 13 age-matched healthy controls. Immune complexes were found to be strongly positive in 27 (71%) of the 38 rheumatic fever patients. Immune complexes were positive in 13 (81.2%) of 16 patients with acute rheumatic fever carditis, in four (50%) of the eight patients with acute rheumatic fever without carditis, in six (66.6%) of the nine patients with inactive rheumatic fever with valvular diseases, in four (80%) of the five patients with rheumatic chorea and in one (7.6%) of the 13 controls. The presence of circulating immune complexes in patients with rheumatic fever may be responsible for the severity of the clinical presentation and the duration of the disease.
Keywords: circulating immune complexes; rheumatic fever; childhood